TANGGAP MAKAN DUA SPESIES RESPO Filicaulis bleekeri Keferst DAN Parmarion pupillaris (Humb.) TERHADAP EKSTRAK KASAR BUAH PINANG, AKAR TUBA, ATAU DAUN SEMBUNG FEEDING RESPONSE OF TWO SLUG SPECIES, Flicaulis bleekeri Keferst and Parmarion pupillaris (Humb.), ON CRUDE EXTRACTS OF BETELNUT SEED, DERRIS ROOT, OR WILD HELIOTROPE LEAF - Apriyanto, Dwinardi; Toha, Burhannudin; Nordat, Iskandar (Pembangunan Pedesaan, 2006)
This study was conducted to determine the effects of crude extracts of betelnut, derris root, or wild heliotrope on the feeding response of two slug species, Filicaulis bleekeri and Parmarion pupillaris. Feeding test was performed in Petri dishes lined with wet white muslin by exposing 3 cm diameter leaf discs of treated -1 chinese cabbage with each extract (concentration of 50 g 100 ml water) to each slug species for 6 days. Control leaf discs were treated with water. Feeding response was measured by weighting leaf disc before and after 24 h feeding totaled into 6 days feeding period. Betel nut extract was further tested outdoor at the -1 concentration of 0 (control), 12.5, 25, and 50 g 100 ml . Filicaulis bleekeri (three slugs for each extract concentration) were released into each bucket and allowed to feed for 6 days. Percentages of leaf damage (consumed) by the slugs were measured at day 2, 4, and 6 after exposure. The results showed that crude extract of betelnut and derris root significantly reduced leaf feeding of F. blekeeri. The effect of betelnut extract was more pronounced than that of derris root. Wild heliotrope extract did not reduce slug feeding. Slug weight decreased in all treatments including control, but not on leaf treated with the heliotrope extract. There was no slug died from feeding on food treated with each extract. Theresponse of P. pupillaris was not conclusive. Betelnut extract reduced leaf damage by F. bleekeri significantly until day four after exposure.